Attitude Towards Green dan Enviromental Friendly Activity sebagai Pendorong untuk Meningkatkan Kunjungan ke Semarang Zoo - Pamuja, Yobel Uri; Athanasius, Sentot Suciarto (Universitas Katolik Soegijapranata, Semarang, 2024)
This research aims to determine interest in revisiting green tourist attractions that preserve the animals at Semarang Zoo. A sample of 96 visitors was taken from the population of all Semarang Zoo visitors. The data collection technique was carried out using a questionnaire. The research results showed that respondents were interested in visiting again and were interested in recommending it to others. The two variables attitude towards green or attitude that cares about the environment and environmental friendly activity or activities that care about the environment have a positive and significant effect on interest in returning to visit. Semarang Zoo should be able to increase the natural beauty of the Semarang Zoo tourist attraction. This can be done by rearranging the plants and arranging the animal enclosures so that it is more comfortable for visitors to walk around and spend more time at Semarang Zoo. It would be better if there are more Instagrammable spots and tags for selfie photos and uploading them on social media